(untitled) (Journal of Applied Oral Science, 2022)
Aiming to kill bacteria in dentin tubules of infected dental pulp cavities, we evaluated the effects of sodium hypochlorite (NaOCl) solution agitated by different irrigation protocols, i.e., conventional needle irrigation (CNI), passive ultrasonic irrigation (PUI), the EDDY tip, and the neodymium-doped yttrium aluminum perovskite (Nd:YAP) laser. The EDDY achieved good antibacterial effects as passive ultrasonic irrigation in the coronal and middle thirds. Nd:YAP laser irradiation and PUI were effective in the apical third of the root canal. Objectives: To evaluate the ability of NaOCl agitated by high-frequency sonic irrigation–EDDY, PUI, and Nd:YAP laser–to kill bacteria in infected root canal walls and if the associated temperature increases at the root surface during application. Methodology: Infected root canal models were established, and roots were randomly divided into six groups: negative control, positive control, CNI, PUI, sonic agitation with EDDY, and Nd:YAP laser groups. After irrigation, the teeth were split and stained using the LIVE/DEAD BacLight Bacterial Viability Kit. Dead bacteria depth was evaluated by a confocal laser scanning microscopy and the temperature at the root surface was assessed using a thermal imaging camera during the irrigation process. Results: In the coronal and middle thirds of the root canal, PUI and EDDY had stronger antibacterial effects than CNI (p<0.05); in the apical third, the antibacterial effects of PUI and Nd:YAP laser-activated irrigation were better than CNI (p<0.05). The maximum change in temperature was significantly greater during continuous Nd:YAP laser application compared with the other methods, but intermittent irrigation helped lessening this trend. Conclusions: NaOCl agitated by EDDY tip and PUI exhibited a similar bacteria elimination effect in the coronal and middle root canal. Nd:YAP laser was effective in the apical third and intermittent irrigation reduced its thermal impact.